Fighting the system? Populist radical right parties and party system change. (March 2014) - Mudde, Cas
This article assesses the impact of populist radical right parties on national party systems in Western Europe. Has the emergence of this new party family changed the interaction of party competition within Western European countries? First, I look at party system change with regard to numerical and numerical–ideological terms. Second, I evaluate the effect populist radical right parties have had on the different dimensions of party systems. Third, I assess the claim that the rise of populist radical right parties has created bipolarizing party system. Fourth, I look at the effect the rise of the populist radical right has had on the logic of coalition formation. The primary conclusion is that, irrespective of conceptualization and operationalization, populist radical right parties have not fundamentally changed party systems in Western Europe.